Los musgos de la Sierra de Alcaparrosa, México - Cardenas S., Angeles; Delgadillo M., Claudio (Instituto de Ecología, A.C., 1992)
The known moss flora of Sierra de Alcaparrosa consists of 84 species and varieties. The Pottiaceae (26 species) and the Bryaceae (10 species) are the families best representad; the remaining inelude between 1 and 4 species in the area. The moss flora ineludes a group of 7 cleistocarpic mosses. Among the six phytogeographical elemente that of wide distribution is the largest. Other important elemente in this moss flora are the endemic (known oniy from México), disjunct (between México and South America; two species are representad in Africa and Australia) and the mesoamerican (distributed from México to northern South America).